An online ASD learning module for pediatric health care professionals. Issue 3 (3rd July 2017) - Burnham Riosa, Priscilla; Greenblatt, Andrea; Muskat, Barbara
Abstract : Purpose: Youth with autism spectrum disorder (ASD) often have co-occurring health care needs and are likely to come into contact with several health care professionals over their lives. At the hospital, youth with ASD may require specialized supports to optimize health care experiences and for medical services to be delivered safely. At present, there is a limited understanding of how to best support this patient population. The purpose of this paper is to develop, implement, and evaluate an online training module for hospital staff about ASD. Design/methodology/approach: To evaluate participants' perceived utility of the learning tool, a post-module survey was administered. Findings: In all, 102 health care professionals and other hospital staff completed the training and evaluation measure. Majority of participants had prior ASD-focused education (66 percent) and had experience working with at least 20 youths with ASD (57 percent). Majority of participants (88 percent) perceived the information from the module to be helpful in their daily work and reported that they learned something new (63 percent). Participants were interested in receiving additional ASD online module training opportunities on topics including: hands-on behavior management strategies, in-hospital resources, guidance on treatment adherence, and ASD training geared specifically to protection services staff. Originality/value: The results from this evaluation have important practice implications for hospital staff working with patients with ASD and their families. Evidence-based strategies were easily accessible for staff and the module can be feasibly built upon and expanded as well as disseminated beyond the current hospital setting.